Time-varying analysis of the heart rate variability during A-phases of sleep: Healthy and pathologic conditions. (February 2018) - Dorantes-Méndez, Guadalupe; Mendez, Martin O.; Alba, Alfonso; Parrino, Liborio; Milioli, Giulia
Highlights: Heart rate variability is assessed during A-phases by means of a time-varying model. A major participation of sympathetic pathway occurs in healthy and NFLE patients. The intensity of the shift towards sympathetic activity is related of A-phase type. The NFLE patients present a weaker autonomic response during A-phases. Abstract: In the present study, a comparison of the heart rate variability (HRV) behavior between healthy subjects and Nocturnal Front Lobe Epilepsy (NFLE) patients was carried out during the A-phases of sleep. The A-phases are short cortical events that interrupt the basal oscillation of the sleep stages and form the cyclic alternating pattern phenomenon. HRV was assessed by means of standard temporal measures and frequency measures based on time-varying autoregressive (TVAR) models. The analysis of HRV, in relation to the A-phases occurrence, was performed selecting two segments: one before the onset of the A-phase and one during the A-phase time. The results showed a significant increment in the heart rate during the A-phases in both, healthy subjects and NFLE patients. In addition, a major participation of the sympathetic nervous system was found in both healthy and pathologic conditions based on the sympatho-vagal index (LF/HF) during A-phases. The intensity of the shift towards sympathetic activity is related of A-phase type, where the largest shift is found in A3 phases. However, the NFLE patients present a weaker autonomic response during A-phases. The results suggest that the autonomic cardiac response related with the surveillance mechanism of NFLE patients is affected.